Pengaruh Model Pembelajaran Problem Solving Terhadap Kompetensi Belajar IPA Peserta Didik Kelas VIII SMP Negeri 13 Padang - Sarah, Sarah; Lufri, Lufri; Sumarmin, Ramadhan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The low learning outcomes of students are caused by several problems encountered during the learning process, such as IPA learning process still used teacher centered and lecturing methode. The result of student learning competence still low result and the teacher hasnât yet used learning models can make student will be active. One effort was made to improve students learning competence by applying problem solving learning models. This study aims to determine the effect of the use of problem solving, learning model to the students learning competence SMP 13 Padang. This study is an experimental research using the design of The Static Group Comparison. The study population is all students of Class VIII  SMPN 13 Padang. Sampling using purposive sampling technique. The control class uses the learning model commonly used in the classroom IE discovery learning model and experimental class using a problem solving learning model. The research instrument used is a test of learning result and affective and skill assessment in the form of observation sheet. Data were analyzed using t-test for knowledge, competence because the data were normally distributed and homogeneously. Data were analyzed using up-test for affective and skill competence.Result of hypothesis test in both classes of sample, found that class which uses problem solving, learning model have positive effect of student learning competence of Class VIII 6 SMPN 13 Padang such as knowledge, affective and skill competence